Response Surface Methodology: The Improvement of Tropical Residual Soil Mechanical Properties Utilizing Calcined Seashell Powder and Treated Coir Fibre - Anggraini V. (MDPI, 2024)
Calcined seashell (CSS) powder and treated coir fibre (CF) are well-established additives for reinforcing poor soils. However, the absence of specific mix designs to optimize the mix additives makes it difficult to predict their combined effect on improving the mechanical behaviour of poor soils. This research explores the use of response surface methods to find the optimal proportions of CSS and CF for enhancing the mechanical properties of a tropical residual soil. This study uses a combination of Analysis of Variance (ANOVA) and regression models to examine how the independent variables of the CSS content, CF content, and curing duration influence the responses of the Unconfined Compressive Strength (UCS), Flexural Strength (FS), and Indirect Tensile Strength (ITS). The findings show that the optimal mix of 9.06% CSS, 0.30% CF, and 12 days of curing significantly improved the UCS, FS, and ITS by roughly six, four, and three times, respectively. Microstructural analysis revealed that the formation of calcium-aluminate-hydrate and calcium-silicate-hydrate are the primary components responsible for the enhanced mechanical properties of the treated soil. 2023 by the authors.